The Returns to Lobbying: Evidence from Local Governments in the "Age of Earmarks". (September 2019) - Gordon, Steven
I measure the returns to lobbying for US local governments in terms of federal earmarks. Because a local government's decision to lobby may be endogenous to receiving an earmark, I instrument for lobbying with local housing prices. Since the time period of my analysis covers the Housing Crisis, I argue that the variation in housing prices over this time was largely exogenous to federal earmark distributions. The strong correlation that I find between housing price growth rates and lobbying provides evidence that local governments lobbied to buffer against impending property tax losses. I find no evidence that lobbying is associated with increased earmark awards overall. However, conditional on selection into receiving an earmark, I do find evidence that lobbying served to increase the size of earmark awards.